Knocking out NEGATIVE REGULATOR OF PHOTOSYNTHESIS 1 increases rice leaf photosynthesis and biomass production in the field. (27th February 2021) - Chen, Faming; Zheng, Guangyong; Qu, Mingnan; Wang, Yanjie; Lyu, Ming-Ju Amy; Zhu, Xin-Guang
Abstract : A combination of bioinformatics analysis and transgenic experiments identifies a negative regulator of leaf photosynthesis in rice. Abstract: Improving photosynthesis is a major approach to increasing crop yield potential. Here we identify a transcription factor as a negative regulator of photosynthesis, which can be manipulated to increase rice photosynthesis and plant biomass in the field. This transcription factor, named negative regulator of photosynthesis 1 (NRP1; Os07g0471900), was identified through a co-expression analysis using rice leaf RNA sequencing data. NRP1 expression showed significantly negative correlation with the expression of many genes involved in photosynthesis. Knocking out NRP1 led to greater photosynthesis and increased biomass in the field, while overexpression of NRP1 decreased photosynthesis and biomass. Transcriptomic data analysis shows that NRP1 can negatively regulate the expression of photosynthetic genes. Protein transactivation experiments show that NRP1 is a transcription activator, implying that NRP1 may indirectly regulate photosynthetic gene expression through an unknown regulator. This study shows that combination of bioinformatics analysis with transgenic testing can be used to identify new regulators to improve photosynthetic efficiency in crops.